Evaluation of the implementation of a differentiated approach in inclusive elementary schools - Devina Kusuma Wardani; Sri Marmoah; Sudiyanto Sudiyanto (Curricula: Journal of Curriculum Development, 2025)
The differentiated learning approach tailors instruction to individual student characteristics, creating a personalized learning experience. However, its implementation in inclusive schools is often suboptimal due to limited teacher competency and time management. This study aims to evaluate the implementation of differentiated learning at SD Alam Aminah Sukoharjo using the Context, Input, Process, Product (CIPP) model. This qualitative evaluative study collected data through observation, interviews, and document analysis involving the principal, class teachers, and special needs teachers. Data validity was ensured through the triangulation of sources and methods, while analysis was conducted through reduction, presentation, and drawing of conclusions. Evaluation using the CIPP model revealed that differentiated learning at SD Alam Aminah was functioning effectively. The context was supported by the school's inclusive vision and mission. Input included teachers, assistants, and adequate facilities. The process was evident in the implementation of differentiation in content, process, product, and the learning environment. The product was associated with improved learning outcomes, particularly in relation to individual abilities. Regular students met curriculum standards, while students with special needs received assistance through the Program Pendidikan Individual (PPI). This proves that differentiated learning is effective in creating an adaptive and inclusive learning environment.   Abstrak Pendekatan pembelajaran berdiferensiasi menyesuaikan karakteristik individu peserta didik untuk menciptakan pengalaman belajar yang menyenangkan. Namun, penerapannya di sekolah inklusif sering kali belum optimal karena keterbatasan kompetensi guru dan pengelolaan waktu. Penelitian ini bertujuan mengevaluasi implementasi pembelajaran berdiferensiasi di SD Alam Aminah Sukoharjo dengan menggunakan model Context, Input, Process, Product (CIPP). Penelitian evaluatif kualitatif ini mengumpulkan data melalui observasi, wawancara, dan analisis dokumen yang melibatkan kepala sekolah, guru kelas, serta guru pendamping khusus. Validitas data dilaksanakan dengan triangulasi sumber dan metode, sementara analisis dilakukan melalui reduksi, penyajian, dan penarikan kesimpulan. Evaluasi dengan model CIPP menunjukkan bahwa pembelajaran berdiferensiasi di SD Alam Aminah berjalan baik. Context didukung visi dan misi sekolah yang inklusif. Input meliputi guru, pendamping, dan fasilitas memadai. Process tampak pada penerapan diferensiasi konten, proses, produk, serta lingkungan belajar. Product terlihat dari peningkatan hasil belajar sesuai kemampuan. Siswa reguler mencapai standar kurikulum, sementara siswa berkebutuhan khusus terbantu melalui Program Pendidikan Individual (PPI). Hal ini membuktikan pembelajaran berdiferensiasi efektif menciptakan lingkungan belajar adaptif dan inklusif. Kata Kunci: evaluasi; model CIPP; pendekatan berdiferensiasi; sekolah inklusi